2016
DOI: 10.1371/journal.pone.0160156
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Healthcare-Related Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Transmission Events Using Combined Genetic and Phenotypic Epidemiology

Abstract: BackgroundSince the year 2000 there has been a sharp increase in the prevalence of healthcare-related infections caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli. However, the high community prevalence of ESBL-producing E. coli isolates means that many E. coli typing techniques may not be suitable for detecting E. coli transmission events. Therefore, we investigated if High-throughput MultiLocus Sequence Typing (HiMLST) and/or Raman spectroscopy were suitable techniques for detectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Epidemiologic data were then compared for patients above the screening thresholds (‘genomically related’) within ST (or ST131 E. coli subclades). Patient pairs were classified according to a modification of previously published definitions 23 as ‘probable transmission’ if on the same ward at the same time, ‘possible transmission’ if admitted to the same ward at a different time (within 60 days), or admitted to the same hospital at the same time; all other patients were classified as ‘unlikely transmission’. Statistical analyses were performed using Stata v16.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiologic data were then compared for patients above the screening thresholds (‘genomically related’) within ST (or ST131 E. coli subclades). Patient pairs were classified according to a modification of previously published definitions 23 as ‘probable transmission’ if on the same ward at the same time, ‘possible transmission’ if admitted to the same ward at a different time (within 60 days), or admitted to the same hospital at the same time; all other patients were classified as ‘unlikely transmission’. Statistical analyses were performed using Stata v16.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in the Netherlands have reported the predominance of bla CTX−M genes in ESC R Enterobacteriaceae , mostly Escherichia coli , among hospital and primary care patients (van der Bij et al, 2011 ; Voets et al, 2012 ; Reuland et al, 2013 ), nursing home residents (Willemsen et al, 2015 ) and humans in the community (van Hoek et al, 2015 ; van den Bunt et al, 2016 ). Among them, E. coli belonging to sequence types (ST)10, ST38, ST69 and ST131 recovered from Dutch individuals have been recently associated with ESC R phenotype (Leverstein-van Hall et al, 2011 ; Overdevest et al, 2011 , 2015 ; van der Bij et al, 2011 ; Voets et al, 2012 ; Reuland et al, 2013 , 2016 ; Huijbers et al, 2014 ; Dohmen et al, 2015 ; van Hoek et al, 2015 ; Willemsen et al, 2015 ; Souverein et al, 2016 ; Voor in 't holt et al, 2016 ). However, data regarding the genetic background, plasmid replicon types and Insertion Sequence (IS) of ESBL/AmpC genes and their plasmid-mediated dissemination among the Dutch human population have been scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the QA method alone does not appear to be suitable to assess reliable discrimination in ESBL-producing isolates and detect CTE. This point has already been reported previously for other methods like high-throughput MLST or Raman spectroscopy [27]. To improve methodology, we decided to combine both methods with epidemiological criteria.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 77%